O Círculo Operário de Barbalha como expressão do catolicismo social na educação e na cultura (1930 - 1964) - Silva, Josier Ferreira da (2009)
The Labor Unions compose the Social Catholicism and settle as a political strategy of Catholicism, supported in the Rerum Novarum encyclical, issued by Pope Leo XII in 1891, which directs the Church intervention in the working world. Opposite to the ideological antagonisms between liberalism and socialism, emerging in the modern industrial society, the Catholic Church claims itself as an alternative form of power, holding a theological and political project. In Brazil, the covenant between the Church and the Vargas Government made possible for Catholicism to recover its religious influence beside public power, which had been lost with the imposition of the republican secular country. In this conjecture, the modernization of the society, marked by industrialization, the conflicts between capital and labor become evident and the first labor unions were created. In this historical context, the Labor Unions spread as Catholic institutions serving the re-Christianization of the society by the Roman Church. Defending this theological project, the unionism engages its cultural and educational actions along the workers, guided by Church\\\\\\\'s dictated documents, aiming the formation of Christian leaderships and the agreement between the classes that tried to settle the Christian Social Order. In the city of Barbalha, this institution acts along the public and canonical power promoting education, music, citizenship and religion, concurring with the national policy conjuncture.